Evaluation of current strategies and future priorities for improving health in developing countries. Issue 7530 (10th November 2005) - Evans, David B; Lim, Stephen S; Adam, Taghreed; Edejer, Tessa Tan-Torres
Abstract : This article is the last in a series examining the cost effectiveness of strategies to achieve the millennium development goals for health